Innominate Artery Stenosis Presenting With Migratory Digital Ischemia. (August 2016) - Juo, Yen-Yi; Ramirez, Lisbi Rivas; Ruben, Garry
Background: Atherosclerotic lesions of the supra-aortic trunk vessels, including the innominate artery, subclavian artery, or the common carotid artery, tend to present either as low-flow state distal to the lesion or as embolic events. The risk of embolic cerebrovascular event complicates the management of this condition via a pure endovascular approach. A combined operative–endovascular intervention may be a valuable approach in order to reduce the risk of intraoperative stroke and prevent future embolic events. Case Presentation: An 84-year-old female presented at the emergency department (ED) with a 4-month history of migratory digital cyanotic lesions across various fingers on her right hand. The lesion eventually progressed into dry gangrene on her right middle finger. Selective angiography of the aortic arch vessels demonstrated significant atherosclerotic plaque burden throughout her supra-aortic vessels and a segmental stenosis at the proximal innominate artery. A right carotid cut down was performed to allow clamping of the carotid artery so as to minimize the risk of intraoperative stroke from plaque manipulation. Retrograde balloon angioplasty was performed, and stent was placed across the stenotic segment. The patient tolerated the procedure well and had an uneventful postoperative course. She was discharged on postoperative day 3. At 2-week follow-up, she has had no progression of her digital ischemia nor other focal cranial nerve deficits. Conclusion: Migratory digital ischemia is a rare presentation of atherosclerotic disease of the supra-aortic vessels. It represents a challenging situation for endovascular intervention due to concern about plaque dislodgment during the procedure. A retrograde balloon-stent angioplasty following distal carotid control with an open approach may be safe and effective in selected patients.